Delayed renal dysfunction and flash pulmonary edema post endovascular abdominal aneurysm repair. Issue 2 (20th October 2015) - Carron, Pierre‐Louis; Piliero, Nicolas; Heitz, Morgane; Kribs, Marc; Rodière, Mathieu; Jousse, Patrick; Gunther‐Calvino, Silvia; Thony, Frédéric
Abstract: After endovascular aortic repair (EVAR), the deterioration in long‐term renal function is probably multifactorial. Preoperative renal failure is an independent risk factor. Postoperative renal dysfunction can be associated with inadvertent renal artery occlusion, renal artery complications as stenosis, plaque dislodgement, or dissection. Ischemic nephropathy can accelerate hypertension and circulatory congestion. We report a case of coverage of the renal arteries symptomatic with flash pulmonary edema and renal failure 15 months after EVAR, suggesting a delayed endograft migration. The patient had complete resolution of symptoms and renal function after renal artery stenting with placement between endograft and aneurysm to the left renal artery.